The Fiscal Effects of Immigration to the UK - Christian Dustmann; Tommaso Frattini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
In this paper, we investigate the fiscal impact of immigration on the UK economy, with a focus on the period since 1995. We provide estimates for the overall immigrant population for the period between 1995 and 2012, and for more recent immigrants who arrived since 2000, distinguishing between immigrants from European versus non-European countries. Overall, our findings indicate that EEA immigrants have made a positive fiscal contribution, even during periods when the UK was running budget deficits. This positive contribution is particularly noticeable for more recent immigrants that arrived since 2000 in particular from EEA countries.
Keywords: J61; J68; H20; 330; Immigration; Fiscal Impact; Welfare State